ITPR1 Mutation Contributes to Hemifacial Microsomia Spectrum - Liu, Zhixu; Sun, Hao; Dai, Jiewen; Xue, Xiaochen; Sun, Jian; Wang, Xudong (Frontiers in Genetics, 2021)
Hemifacial microsomia (HM) is a craniofacial congenital defect involving first and second branchial arch, mainly characterized by ocular, ear, maxilla-zygoma complex, mandible, and facial nerve malformation. HM follows autosomal dominant inheritance. Whole-exome sequencing of a family revealed missense mutation in a highly conserved domain of ITPR1. ITPR1 is a calcium ion channel. By studying Itpr1’s expression pattern, we found that ITPR1 participated in craniofacial development, especially the organs corresponded to the phenotype of HM. In zebrafish, itpr1b, which homologous to human ITPR1, is closely related to craniofacial bone formation. The knocking down of itpr1b in zebrafish could lead to a remarkable decrease of craniofacial skeleton formation. qRT-PCR suggested knockdown of itpr1b could increase the expression of plcb4 while decreasing the mRNA level of Dlx5/6. Our findings highlighted ITPR1’s role in craniofacial formation for the first time and suggested ITPR1 mutation contributes to human HM.